Grit, academic resilience, and mindset of nursing students: A cross-sectional study - Boitumelo Setlogelo; Champion N Nyoni (Elsevier, 2024)
Background: Nursing students engage with the complex health system for competence development. These students are exposed to nerve-wrecking experience in addition to their everyday personal and social challenges. Non-cognitive attributes, namely grit, resilience and mindset can influence students' ability to overcome complexities as they become nurses resulting in academic success and well-being. Insights into the state of non-cognitive attributes among undergraduate nursing students are essential in developing tailor-made educational programmes to enhance their grit, resilience, and mindset. Objectives: To describe the undergraduate nursing students' grit, academic resilience, and mindset at a university in South Africa Design: A quantitative descriptive cross-sectional design. Setting: A School of Nursing at a public multi-campus university in South Africa. Participants: All students (N = 315) registered for the undergraduate nursing programme were invited to participate, and 70 % (N = 221) chose to participate. Methods: Data were collected using self-administered questionnaires that included a 7-item demographic survey, the 30-item Academic Resilience Scale (ARS-30) that measures affective, cognitive, and behavioural responses in an educational context, the 16-item Dweck Mindset Scale (DMI) that measures a personal belief about whether intelligence and talent are fixed or amenable to change, and the 8-item Grit-S scale measuring passion for long term goals and perseverance. The collected quantitative data were analysed statistically through the Statistical Analysis Software Version 9.4 computer programme. Findings: The findings revealed that the participants have normal grit and a growth mindset, but low academic resilience. Conclusions: Tailor-made educational programmes that target non-cognitive attributes must integrate interventions that are focused on enhancing academic resilience for undergraduate nursing students.